2011
DOI: 10.1074/jbc.m111.258772
|View full text |Cite
|
Sign up to set email alerts
|

The IQGAP1 Protein Is a Calmodulin-regulated Barbed End Capper of Actin Filaments

Abstract: IQGAP1 is a large modular protein that displays multiple partnership and is thought to act as a scaffold in coupling cell signaling to the actin and microtubule cytoskeletons in cell migration, adhesion, and cytokinesis. However the molecular mechanisms underlying the activities of IQGAP1 are poorly understood in part because of its large size, poor solubility and lack of functional assays to challenge biochemical properties in various contexts. We have purified bacterially expressed recombinant human IQGAP1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 59 publications
(31 reference statements)
2
63
1
Order By: Relevance
“…4B and supplementary material Table S3). In addition to Rac1 and RhoA, there is evidence that IQGAP1 can recruit and regulate other small GTPases including Cdc42 (Bashour et al, 1997;Kuroda et al, 1996), Arf6 (Hu et al, 2009) and Rap1 (Awasthi et al, 2010;Jeong et al, 2007) and their downstream effectors (supplementary material Table S3) (Noritake et al, 2004;Pelikan-Conchaudron et al, 2011;Sakurai-Yageta et al, 2008). A recurring theme from these studies, and from ours, is that modulation of GTPase activity by IQGAP1 is due to the recruitment of other proteins.…”
Section: Discussionmentioning
confidence: 83%
“…4B and supplementary material Table S3). In addition to Rac1 and RhoA, there is evidence that IQGAP1 can recruit and regulate other small GTPases including Cdc42 (Bashour et al, 1997;Kuroda et al, 1996), Arf6 (Hu et al, 2009) and Rap1 (Awasthi et al, 2010;Jeong et al, 2007) and their downstream effectors (supplementary material Table S3) (Noritake et al, 2004;Pelikan-Conchaudron et al, 2011;Sakurai-Yageta et al, 2008). A recurring theme from these studies, and from ours, is that modulation of GTPase activity by IQGAP1 is due to the recruitment of other proteins.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, FGD6 may regulate the interactions of integrins with different F-actin meshworks. Another FGD6 interactor is IQGAP1, which binds Cdc42 (37) and has barbed end capping activity of actin filaments (38). IQGAP1 contains an atypical phosphoinositide binding domain at its C terminus allowing its binding to PI(3,4,5)P 3 (39,40), consistent with its localization to podosomes/sealing zones of osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…4) although this particular function of IQGAP1 in cells has not been addressed. Carlier and colleagues found that IQGAP1 purified from bacteria, caps the barbed ends with a higher affinity for the ADP-bound terminal subunits in actin filaments (Pelikan-Conchaudron et al, 2011). In addition, this activity depends on the C-terminal half of IQGAP1 and the capping activity is inhibited by calmodulin irrespective of the Ca 2+ concentration.…”
Section: Regulation Of Actin Dynamics By Iqgap1mentioning
confidence: 99%